2023
DOI: 10.1111/1749-4877.12705
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the divergent evolution of the oceanic squid Sthenoteuthis oualaniensis (Cephalopoda: Ommastrephidae) from the Indian Ocean

Abstract: Sthenoteuthis oualaniensis is known for its complex population structure with three major transoceanic forms (viz. middle‐sized, dwarf, and giant forms) whose taxonomic status has been disputed for decades. This integrated taxonomic study examines these prevenient morphotypes gathered on cruises in the Indian Ocean to ascertain their status in the evolutionary history of the species. Molecular analyses employing mitochondrial (COI, ND2) and nuclear (H3) markers revealed four genetically distinct and novel line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The results in February and December were poor, and the fishing efforts in suitable habitats accounted for more than 60% of the total, which was lower than that in other months. At the same time, according to the superimposed map of habitat suitability index and CPUE value in 2019, the distribution range of suitable habitat for northern Indian Ocean S. oualaniensis was roughly 12~18 • N and 55~65 • E. This is also the main distribution area indicated by scholars studying the central fishing ground for S. oualaniensis in the northern Indian Ocean [34,35]. The range of suitable habitat in February was concentrated in the north.…”
Section: Analysis Of Habitat Suitability Index Model Of S Oualaniensismentioning
confidence: 91%
“…The results in February and December were poor, and the fishing efforts in suitable habitats accounted for more than 60% of the total, which was lower than that in other months. At the same time, according to the superimposed map of habitat suitability index and CPUE value in 2019, the distribution range of suitable habitat for northern Indian Ocean S. oualaniensis was roughly 12~18 • N and 55~65 • E. This is also the main distribution area indicated by scholars studying the central fishing ground for S. oualaniensis in the northern Indian Ocean [34,35]. The range of suitable habitat in February was concentrated in the north.…”
Section: Analysis Of Habitat Suitability Index Model Of S Oualaniensismentioning
confidence: 91%
“…Similarly, three populations with distinguishable size ranges were identified (Yatsu, 1997). Recently, Jeena et al (2023) reported four genetically distinct and novel lineages of S. oualaniensis in the Indian Ocean, representing three morphotypes from the Arabian Sea (dwarf forms, giant form, and middle-sized forms). The maximum mantle length (ML) of S. oualaniensis is reported as 690 mm dorsal mantle length (DML), and the life span is about 0.5 to 1 year (Trotsenko and Pincukov, 1994).…”
Section: Introductionmentioning
confidence: 99%